6(2+7x)+3x=9+6(9+8x)

Simple and best practice solution for 6(2+7x)+3x=9+6(9+8x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2+7x)+3x=9+6(9+8x) equation:


6(2+7x)+3x=9+6(9+8x)

We simplify the equation to the form, which is simple to understand
6(2+7x)+3x=9+6(9+8x)

Reorder the terms in parentheses
+(+12+42x)+3x=9+6*(9+8x)

Remove unnecessary parentheses
+12+42x+3x=+9+6+*(+9+8x+)

Reorder the terms in parentheses
+12+42x+3x=9+(+54+48x)

Remove unnecessary parentheses
+12+42x+3x=+9+54+48x

We move all terms containing x to the left and all other terms to the right.
+42x+3x-48x=+9+54-12

We simplify left and right side of the equation.
-3x=+51

We divide both sides of the equation by -3 to get x.
x=-17

See similar equations:

| (2x+4y)+(2x-y)-(x-2y)= | | 16-(3x-15)=4x-(9x-9) | | 3=8x-7x+4 | | y^3(3-4x^2)=7x-y^4 | | 2(x+3/4)=9(1/6-x) | | -8x+9x+6=9 | | 6x-8x+2=-13 | | 35=x+(2x-1)+(3(2x-1)+3) | | 35=x+(2x-1)+(3(2x-1)+2) | | 35=x+(3x-1)+(4(3x-1)+2) | | x(x+5)+1=(x+6)(x+6) | | 7=r^(1/2) | | 6x-3-5x=-13-5 | | 2cotx/sinx | | 35=x+(3x-1)+(2(2x-1)+2) | | M/10=4 | | 8x-7x-6=7-13 | | 10(x+2/15)=8(x-7/3) | | 35=x+(2x-1)+(4(2x-1)+2) | | 9x-16=3x+20 | | X/2=50 | | 4x-5=3x-3 | | -5=7x+1-6x | | 35=x+(2x-1)+(14(2x-1)+2) | | 115+5x=240 | | 3.5x+5=50.50 | | -15=-6r-1-2 | | 25x+57=232 | | M^(3/4)=27 | | 15x-17+2x=-34 | | 5x+9-4x=-1 | | 5x-1=4x-4 |

Equations solver categories